Vertical structure and kinematics of the LMC disc from SDSS/Gaia - Jiménez-Arranz, O.; Horta, D.; Van Der Marel, R. P.; Nidever, D.; Laporte, C. F.P.; Patel, E.; Rix, H. W. (Astronomy and Astrophysics, 2025)
Context. Studies of the internal kinematics of the LMC have provided a detailed view of its structure, largely thanks to the exquisite proper motion data supplied by the Gaia mission. However, line-of-sight (LoS) velocities, the third component of the stellar motion, are only available for a small subset of the current Gaia data, thus limiting studies of the kinematics perpendicular to the LMC disc plane. Aims. We synergise new SDSS-IV/V LoS velocity measurements with existing Gaia DR3 data, increasing the 5D phase-space sample by almost a factor of three. Using this unprecedented dataset, we interpret and model the vertical structure and kinematics across the LMC disc. Methods. We first split our parent sample into different stellar types (young and old). We then examined maps of vertical velocity, vz′, moments (median and median absolute deviation) perpendicular to the LMC disc out to R′ ≈ 5 kpc. We also examined the vertical velocity profiles as a function of disc azimuth and radius. We interpret our results in the context of three possible scenarios: (1) time variability in the orientation of the disc symmetry axis; (2) use of an incorrect LMC disc plane orientation; or (3) the presence of warps or twists in the LMC disc. We also present a new inversion method to construct a continuous 3D representation of the disc from spatially resolved measurements of its viewing angles. Results. Using young stellar populations, we identify a region in the LMC arm with highly negative vz′;; this region overlaps spatially with the supershell LMC 4. When interpreting the maps of vz′, our results indicate that (1) the LMC viewing angles may vary with time due to precession or nutation of the spin axis for example. However, this cannot explain most of the structure in the vz′ maps. (2) When re-deriving the LMC disc plane by minimising the RMS vertical velocity vz′ across the disc, the inclination and line-of-nodes position angle are i = 24′ and Ω = 327′, respectively, with an ∼ 3° systematic uncertainty associated with sample selection, contamination, and the position of the LMC centre. (3) When modelling in concentric rings, we obtain different inclinations for the inner and outer disc regions, and when modelling in polar segments, we obtain a quadrupolar variation as a function of azimuth in outer the disc. We provide 3D representations of the implied LMC disc shape. These provide further evidence for perturbations caused by interaction with the SMC. Conclusions. The combination of SDSS-IV/V and Gaia data reveal that the LMC disc is not a flat plane in equilibrium but that the central bar region is tilted relative to a warped outer disc.
Publisher Copyright: © The Authors 2025.
Keywords: Galaxies: kinematics and dynamics; Galaxies: structure; Magellanic Clouds